The Role of Interpersonal Relationships in Adolescents' Suicidal Behavior: A Qualitative Analysis of Semi-Structured Interviews - Polskaya, N.A.; Yakubovskaya, D.K.; Sharova, D.A.; Basova, A.Ya (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2024)
This article presents the results of a qualitative analysis based on semi-structured interviews conducted with adolescents (n=13, aged 13-17), who were admitted to an inpatient psychiatric facility after attempted suicide. Content analysis yielded groups of words describing the circumstances of the suicide attempt based on semantic proximity. The following groups emerged (ordered by descending frequency of use): words describing one's psychological state, descriptions of family and relatives, words related to studies, school or college, and descriptions of relationships with peers. Within the framework of the thematic analysis, two superordinate themes and nine subthemes were identified, revealing the subjective experience of the suicide attempt. The first superordinate theme, psychological distress, includes the subthemes of "negative thoughts and emotions", "mental pain" and "fear of surviving". The second superordinate theme, interpersonal vulnerability, includes the subthemes of "feeling misunderstood by loved ones", "conflicts", "loneliness", "experiencing the loss of important relationships", "self-destructive way of communicating problems", "the excessive importance of emotional relationships with peers" and "sensitivity". These findings suggest that interpersonal relationships may play a significant role in adolescents' suicide attempts, including both family relationships (primarily relationships with mothers) and relationships with peers; moreover, the state of psychological distress is described by adolescents in direct connection with dissatisfaction with interpersonal relationships (conflicts, rejection, neglect). Thus, interpersonal vulnerability, along with psychological distress, is one of the key characteristics of adolescent suicides. Работа направлена на изучение роли межличностных отношений в суицидальном поведении подростков. Представлены результаты качественного анализа полуструктурированных интервью, которые проведены с подростками, госпитализированными после суицидальной попытки в психиатрический стационар (N=13, 13-17 лет). На основе контент-анализа были выделены группы семантически связанных слов, характеризующих: (1) текущее психологическое состояние; (2) отношения в семье и с родственниками; (3) обучение в школе/колледже; (4) отношения со сверстниками. В рамках тематического анализа были выделены две ключевые темы и девять категорий, раскрывающие субъективный опыт переживания суицидальной попытки. Первая тема - психологический дистресс - объединила категории «негативные мысли и эмоции», «чувство душевной боли» и «страх выжить». Вторая тема - межличностная уязвимость - объединила категории «чувство, что близкие не понимают», «ссоры», «одиночество», «переживание утраты близких отношений», «аутодеструктивный способ сообщения о проблемах», «сверхзначимость эмоциональных отношений со сверстниками» и «ранимость». Значительная роль в субъективном опыте переживания суицидальной попытки отводится межличностным отношениям, включая как отношения в семье (особенно отношения с матерью), так и отношения со сверстниками, а состояние психологического дистресса описывается подростками в прямой связи с неудовлетворенностью в межличностных отношениях (ссорами, отвержением, пренебрежением). Таким образом, межличностная уязвимость, наряду с психологическим дистрессом, выступает одной из ключевых характеристик подростковых суицидов.